Canon EOS digital Rebel XT guide to digital SLR photography - Busch, David D. (Thomson Course Technology, 2007)
Canon EOS Digital Rebel XT Guide to Digital SLR Photography serves as a concise introduction to the features of theCanon EOS dSLR. This book not only covers the camera's basic controls, it explains their purpose and function, outlining how readers should use them and why. From focus zones to zoom settings, to exposure modes, The Canon EOS Digital Rebel XT Guide to Digital SLR Photography is aimed at providing photographers with a concise, yet complete, introduction to all aspects of digital shooting. For anyone who would otherwise struggle to learn how to use their Canon 30D's basic capabilities, this book is a quick start to pixel proficiency